Pulmonary exacerbations in insured patients with bronchiectasis over 2 years - Patrick A. Flume; Joseph Feliciano; Matthew Lucci; Jasmanda Wu; Sebastian Fucile; Mariam Hassan; Anjan Chatterjee (ERJ Open Research, 2023)
Background Patients with bronchiectasis experience persistent symptoms and frequent pulmonary exacerbations; this study investigated the frequency of exacerbations and all-cause hospitalisation. Methods This longitudinal, retrospective, claims database study (IBM® MarketScan®) identified patients aged ≥18 years from 1 July 2015 through 30 September 2018. Exacerbations were identified by bronchiectasis inpatient claim or a healthcare interaction, followed by antibiotic prescription within 7 days. Patients with ≥36 months of continuous health plan enrolment (12 months preceding the first bronchiectasis claim, i.e., baseline period and ≥24 months of follow-up) were included. Patients with cystic fibrosis at baseline were excluded. A multivariable logistic regression model identified baseline factors associated with having ≥2 exacerbations over the 2-year follow-up period. Results In total, 14 798 patients with bronchiectasis were identified; 64.5% were female, 82.7% were aged ≥55 years and 42.7% had ≥2 exacerbations at baseline. Having ≥2 exacerbations after 2 years was positively associated with chronic macrolide use, long-acting β2 agonist use, gastro-oesophageal reflux disease, heart failure and Pseudomonas aeruginosa. Frequent exacerbations (≥2) at baseline were significantly associated with greater likelihood of experiencing ≥2 exacerbations during the first and second year's follow-up (unadjusted odds ratios 3.35 (95% CI 3.1–3.6) and 2.96 (95% CI 2.8–3.2), respectively). The proportion of patients experiencing ≥1 all-cause hospitalisation cumulatively increased from 41.0% in the first year of follow-up to 51.1% over 2 years' follow-up. Conclusion Frequent exacerbations in patients with bronchiectasis may increase the likelihood of future exacerbations over 2 years of follow-up, with increased hospitalisation rates over time.